Professional identity of the general physician: lessons to be applied by the medical school - Franco de Sá, Ronice (ABCS Health Sciences, 2015)
Introduction: Construction of professional identity is not only a process of relationship between individuals. Objective: To know the construction of the professional identity of young general practitioners through examination of the articulation of biographical and relational transactions involving primary socialization (family environment) and secondary (educational institution and early careers). Methods: We conducted document analysis and in‑depth interviews with ten general practitioners trained by the same university and eight key informants’ teachers to validate the field. It used modeling for analysis by conceptual categories. It was considered generalist career as a general practice, family medicine, public health and/or collective. Results: Drew up a model where the general practitioner emphasizes the focus on the user, reinforces family values linked to altruism, personal autonomy, honesty and focus on studies. In secondary socialization he/she lives identity conflict within the educational institution the elitist education, meritocratic focusing on specialization. The student shows relations with political and social engagement and approach with secular culture. At the beginning of professional practice, the student faces the fight between the values offered by the media as subordination to the market, lack of time, career choice of prestige and values preferred by the general focus on the other, interaction with other professionals, , prioritization of knowledge‑being and know‑how. Conclusion: It is confirmed that the educational institution plays a fundamental role in guiding the career choice and can strengthen the choice by generalist careers by introducing reflective practice, and relationship with other knowledge such as art, culture, politics, and philosophy.